PERBANDINGAN NILAI GCS, TEKANAN DARAH, DAN LUARAN TERHADAP LOKASI PERDARAHAN PADA PASIEN STROKE ICH DEWASA MUDA DI RSUD DR. SOETOMO SURABAYA - Nuzula Fikrin Nabila, NIM011411131124 (2017)
Introduction: ICH (intracerebral hemorrhage) is a catastrophic medical emergency with high mortality and morbidity which accounts for 15-20% of all strokes. However, studies regarding clinical characteristics and outcome of young ICH patients is limited due to its low incidence. Thus, this study aims to analyze differences of GCS score, blood pressure, and clinical outcome between young adult ICH patients with different ICH location. Methods: The study was designed as a cross-sectional study. Differences of GCS score and blood pressure at admission were assessed using Kruskal-Wallis test, while comparison of the clinical outcome was assessed using chi-square test. Result: This study included 90 of 120 patients with primary ICH of both sexes aged between 25-44 years in Dr. Soetomo General Hospital Surabaya from 2014 until 2015. From the analyses, differences of GCS score (p=0,044) and outcome (p=0,002) were identified among different ICH locations. The lowest GCS score median was found in brainstem ICH (med=5), while the highest was in basal ganglia/capsular (med=13). The highest mortality was in brainstem (80%), followed by thalamic (67%) ICH, while the lowest was in basal ganglia/capsular (24%), followed by lobar (28%) ICH. There was no significant differences of systolic (p=0,566) and diastolic (p=0,680) blood pressure among different ICH location. Conclusion: GCS score at admission and outcome, but not blood pressure at admission, are significantly different in young adult patients with different ICH location. It is still a need to conduct a study on functional outcome and the most proper treatment for young adult patients with different ICH location.